On boxes, contents, and users: food security and the WTO negotiations - Díaz-Bonilla, Eugenio; Robinson, Sherman; Thomas, Marcelle (International Food Policy Research Institute, 2002)
An important component of the current debate about agriculture trade negotiations is whether further liberalization of trade and agricultural policies may help or hinder food security in WTO member countries. These concerns were formulated first, in Article 20 of the Agreement on Agriculture negotiated during the Uruguay Round, which indicated that negotiations should take into consideration, among other things, "non trade concerns"; and in its preamble, which mentioned as examples of those concerns, "food security and the need to protect the environment". They were also reaffirmed in the Doha Declaration, which declares that "the long-term objective" is "to establish a fair and market-oriented trading system through a program of fundamental reform", and confirmed that special and differential treatment will be granted to developing countries "to effectively take account of their development needs, including food security and rural development". Although the issue of food security and agricultural negotiations within the WTO has been raised both by industrialized ("multifunctionality" of agriculture) and developing countries, the discussion in the case of developing countries has included important policy objectives such as elimination of poverty and hunger (as cause and consequence of food insecurity). Concerned with the effects that further negotiations would have on the attainment of those objectives in poor countries, several developing countries have proposed the creation of a "Development Box" or a "Food Security Box". To contribute to this debate, the paper surveys and discusses in greater detail three main aspects of trade liberalization and food security within the WTO: the adequacy of the current WTO classification of countries according to their food security situation; the policy perspectives in industrialized countries and in developing countries; and the legal issues faced by developing countries. The paper concludes that a better classification is needed within the WTO to target food insecure countries, that many food security concerns can be addressed with specific clarifications and changes in the current language of the AoA, and that although developing countries may not be legally constrained to invest in food security, they lack the financial, human, and institutional resources to do so.